Dimension Synthesis and Optimized FOPID Control of the Delta Robot with Moth Swarm Algorithm - Yigit, Tevfik; Celik, Hakan (Springer Heidelberg, 2023)
In this study, Delta robot that one of the most studied and used robot and has distinctive advantages and parallel structure, has been optimized in point of dimensions. 3D solid model of the optimized robot model transferred to MATLAB/Simulink environment. Dimensions of the Delta robot have been obtained to ensure desired workspace with minimum dimensions with moth swarm algorithm (MSA) optimization and particle swarm optimization (PSO). Widely known PSO algorithm has been used for the measure to the performance of the MSA algorithm that is new to the literature. Joints of the robot actuated with the brushless DC (BLDC) motors. System has been controlled fractional-order PID (FOPID) controller. Also integer-order PID controller (IOPID) has been used to clearly see the performance of the FOPID with the aim of comparison. Parameters of both of these controllers are optimized with MSA optimization in equal conditions. When the optimization cost results and the performance test results are examined, it is seen that the FOPID controller performed better than IOPID controller. Designed Delta robot system has been tested with different scenarios, and robotic system has been achieve that this scenarios with high performance.
Keywords: Delta robot; Dimension synthesis; Fractional-order PID; Moth swarm algorithm